NETWORK TRAFFIC QUEUE ANALYSIS - Olimov, Olimboy Otabekovich; Saparbayev, Raxmon Komiljonvich (Educational Research in Universal Sciences, 2024)
In this paper we provide a framework for analyzing network traffic traces through trace-driven queueing. We also introduce several queueing metrics together with the associated visualization tools (some novel) that provide insight into the traffic features and facilitate comparisons between traces. Some techniques for non-stationary data are discussed. Applying our framework to both real and synthetic traces we i) illustrate how to compare traces using trace-driven queueing, and ii) show that traces that look “similar” under various statistical measures (such as the Hurst index) can exhibit rather different behavior under queueing simulation. This paper deals with assessing and comparisons the real it is known for everyone that nowadays the services of the telecommunication networks are being developed day-to-day. The acceptable way of transmission data with the high quality, effect and safety through the network is to use the packet switching in the network. The main part of telecommunication networks is considered communication links. Through these communication links the information in the shape of packets is transmitted and during the transmission these packets pass some intermediate nodes. These intermediate nodes contain routers or switches, etc. By those intermediate nodes a lot of packet streams coming to the different nodes pass and in order not to be served to them at the same time the packets are curried in buffer in a queue. Then they are served in turn. In this condition packet loss and delay processes occur at intermediate nodes and this induces the decrease of the quality of service (QoS) in the network. This paper deals with the processes of packet losses occured in telecommunication networks in detail. Moreover, while researching the processes of packet losses, this network is modeled in AnyLogic program.